1995
DOI: 10.1017/s0952523800007380
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity in dyslexia

Abstract: Contrast sensitivity was determined for dyslexic and normal readers. When testing with temporally ramped (i.e. stimuli with gradual temporal onsets and offsets) gratings of 0.6, 4.0, and 12.0 cycles/deg, we found no difference in contrast sensitivity between dyslexic readers and controls. Using 12.0 cycles/deg gratings with transient (i.e. abrupt) onsets and offsets, we found that dyslexic individuals had, compared to controls, markedly inferior contrast sensitivity at the shortest stimulus durations (i.e. 17,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 47 publications
(70 reference statements)
0
43
0
Order By: Relevance
“…Either or both of these factors would decrease their ability to detect global coherent motion and would be consistent with anatomical evidence of structural impairment in both the retino-cortical M-pathway and within the extrastriate dorsal stream of dyslexics [18,28,44]. However, other studies have suggested that sensory de®cits in dyslexia are associated more with a problem detecting short duration stimuli whether they are dynamic or not ( [19,20] for review see [17]). Such a de®cit would be dicult to reconcile with the hypothesis of a visual de®cit speci®c to the M-stream.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Either or both of these factors would decrease their ability to detect global coherent motion and would be consistent with anatomical evidence of structural impairment in both the retino-cortical M-pathway and within the extrastriate dorsal stream of dyslexics [18,28,44]. However, other studies have suggested that sensory de®cits in dyslexia are associated more with a problem detecting short duration stimuli whether they are dynamic or not ( [19,20] for review see [17]). Such a de®cit would be dicult to reconcile with the hypothesis of a visual de®cit speci®c to the M-stream.…”
Section: Introductionmentioning
confidence: 69%
“…Sensitivity for these stimulus parameters are usually unimpaired in dyslexics [10,28,31,33,34]. Some psychophysical studies have failed to con®rm that such visual de®cits are associated with dyslexia ( [20,21,61], see also, [17] for review). Nevertheless most experimental evidence is consistent with the hypothesis that the M (or transient) pathway is a locus of their subtle visual impairments (for reviews see [29,30,56]).…”
Section: Introductionmentioning
confidence: 99%
“…Negative findings of overall group differences in sensory processing have also been reported (e.g. Gross-Glenn et al, 1995;Walther-M . u uller, 1995;Hill et al, 1999), suggesting that differences in sample selection might mediate some of the different patterns of result found across studies.…”
Section: Caveats: Links Between Sensory Processing and Literacy Skillsmentioning
confidence: 90%
“…Numerous researchers have found that dyslexic and nondyslexic controls exhibit different patterns of sensitivity to spatial frequencies (e.g., Borsting et al, 1996;Cornelissen, 1993;Demb, Boynton, Best, & Heeger, 1998;Evans, Drasdo, & Richards, 1993, 1996Gross-Glenn et al, 1995;Lovegrove, Bowling, Badcock, & Blackwood, 1980;Lovegrove et al, 1982;Martin, Cornelissen, Fowler, & Stein, 1993;Martin & Lovegrove, 1984. In particular, studies indicate that dyslexic individuals have reduced sensitivity to certain spatial frequencies and that this reduction tends to be greatest in the low-to midfrequency range (i.e., between 2 and 8 cpd; Borsting et al, 1996;Cornelissen, 1993;Demb et al, 1998;Evans et al, 1993Evans et al, , 1996Lovegrove et al, 1980;Lovegrove et al, 1982, Experiment 2;Martin & Lovegrove, 1984see Skottun, 2000, for a review).…”
mentioning
confidence: 99%